Penyusunan Sistem Informasi Mahasiswa - Nevia Bahruddin; Celyn Cecillia Andita (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2023)
The rapid development of information and communication technology is beneficial to all areas of life, where through information technology the process of collecting, processing data to presenting information becomes very fast, precise and accurate. This development makes computer science an integral part of human life.